Pendopan Filem Sol-gel dengan Fenolftalein: Potensi Penggunaan sebagai Penderia CO2 - Ahmad, Musa; Quah, Ai Ling (Universiti Putra Malaysia Press, 1997)
Transparent film prepared by using sol-gel process was used in this study for entrapment of phenolphthalein. Two coating methods were used for film preparation, Le. dip-coating and spin-coating. The types of solid supports used in this study included filter paper, acetate sheet and slide glass. Qualitatively, phenolphthalein in the immobilised form still maintains its chemical characteristic towards CO2 as in solution. Entrapped reagent in sol-gel film with filter paper as a supporting material was found to give the longest response time although the colour change of the reagent in the presence of CO2 gas was still positive. A morphology study using a scanning electron microscope also indicated that sol-gel film prepared on filter paper as a support experienced more severe cracking problems than the other supports. Results obtained from this study indicate that phenolphthalein immobilised in thin film prepared via sol-gel process is non-leachable and gives reversible response towards CO2 gas.